2020
DOI: 10.1007/s40820-020-00432-2
|View full text |Cite
|
Sign up to set email alerts
|

Environment-Stable CoxNiy Encapsulation in Stacked Porous Carbon Nanosheets for Enhanced Microwave Absorption

Abstract: Magnetic/dielectric@porous carbon composites, derived from metal–organic frameworks (MOFs) with adjustable composition ratio, have attracted wide attention due to their unique magnetoelectric properties. In addition, MOFs-derived porous carbon-based materials can meet the needs of lightweight feature. This paper reports a simple process for synthesizing stacked CoxNiy@C nanosheets derived from CoxNiy-MOFs nanosheets with multiple interfaces, which is good to the microwave response. The CoxNiy@C with controllab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
98
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 238 publications
(99 citation statements)
references
References 45 publications
1
98
0
Order By: Relevance
“…Yet, the continued development of microwave absorbing materials is imperative. These materials are highly utilized in the defense [ 16–22 ] and telecommunications industries, [ 18,23–27 ] as means for reducing radar cross sections for stealth technology, [ 28,29 ] and providing electromagnetic interference shielding for the information processing and transport capabilities in electronic devices. The progression of research and development in the field of MAMs continues to accelerate, and researchers are in need of new methods for materials development and analysis.…”
Section: Figurementioning
confidence: 99%
“…Yet, the continued development of microwave absorbing materials is imperative. These materials are highly utilized in the defense [ 16–22 ] and telecommunications industries, [ 18,23–27 ] as means for reducing radar cross sections for stealth technology, [ 28,29 ] and providing electromagnetic interference shielding for the information processing and transport capabilities in electronic devices. The progression of research and development in the field of MAMs continues to accelerate, and researchers are in need of new methods for materials development and analysis.…”
Section: Figurementioning
confidence: 99%
“…At the same time, the ε′ value of the CNA900 sample decreased from 9.32 to 5.47 during the working frequency from 2 to 18 GHz, while the ε″ value decreased from 5.10 to 2.25. It can be found that the ε′ and ε″ values of CNA800 and CNA1000 accompanied with dramatic fluctuations during high frequency range, which can be ascribed to dielectric resonance behavior and dipole polarization caused by particles aggregation 22 . Moreover, the average values of the real (μ′) and imaginary (μ″) permeability of CNA900 are 1.08 and 0.15, separately.…”
Section: Resultsmentioning
confidence: 97%
“…With an increase in sample thickness, the maximum RL moved toward the low frequency. The matched frequency ( f m ) and matched thickness ( t m ) can satisfy the equation: [ 15 ] tm=nc/(4fm||μr||εr), in which c is the EM wave velocity in free space ( n = 1, 3, 5...). The absorption band (RL less than –20 dB) was over 3–18 GHz, which mainly focused on λ/4.…”
Section: Resultsmentioning
confidence: 99%
“…To achieve thin absorbers, the permeability and permittivity can be improved according to the equation tm=nλ/4=nc/4fmμrεr. [ 15 ] Numerous studies have been conducted on this issue, and found that the modulation of absorbent dimension, structure, component, defect, and surface‐interface can remarkably increase the permittivity owing to the increased multiple polarizations. [ 16–18 ] In addition, based on Snoek's law false(μs1false)fr=23γ×4πMs, the permeability can be enhanced by selecting magnetic materials as absorbers, combining nonmagnetic absorbers with magnetic materials, [ 19,20 ] inhibiting eddy current effects, [ 21 ] enlarging the anisotropic field, [ 8 ] adding an epactal geometrical field to the scattered spin waves, [ 22 ] etc.…”
Section: Introductionmentioning
confidence: 99%